2019
DOI: 10.1177/0897190019882869
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led Annual Wellness Visits: A Review

Abstract: Objective: To summarize findings of pharmacist involvement with Medicare Annual Wellness Visits (AWV), including the number of pharmacist interventions, patient/provider satisfaction, and billing models. Data Sources: A literature search was conducted using PubMed, ScienceDirect College Edition Journals Collection-Health and Life Sciences, Cochrane Library, CINAHL, Medline, and Academic Search Complete, including dates between January 01, 2011, and November 05, 2018. Study Selection: Search was limited to full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…23 In some practices pharmacists provide AWVs. 24 In many medical practices, elements of the AWV are completed by the patient or a caregiver prior to the visit, using selfreported survey questionnaires. Medical assistants or other members of the care team may conduct specific required elements prior to the patient being seen by an eligible provider.…”
Section: Providing Annual Wellness Visits For Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In some practices pharmacists provide AWVs. 24 In many medical practices, elements of the AWV are completed by the patient or a caregiver prior to the visit, using selfreported survey questionnaires. Medical assistants or other members of the care team may conduct specific required elements prior to the patient being seen by an eligible provider.…”
Section: Providing Annual Wellness Visits For Older Adultsmentioning
confidence: 99%
“…Medicare specifies that AWVs can be independently provided by a variety of licensed practitioners, including “a physician, qualified non‐physician practitioner, medical professional (including a health educator, registered dietitian, nutrition professional, or other licensed practitioner), or team of such medical professionals who are working under the direct supervision of a physician.” 23 In some practices pharmacists provide AWVs 24 . In many medical practices, elements of the AWV are completed by the patient or a caregiver prior to the visit, using self‐reported survey questionnaires.…”
Section: Providing Annual Wellness Visits For Older Adultsmentioning
confidence: 99%
“…This correlation can help to surpass many of the current milestones in the pharmaceutical field and could lead to a better relationship in the physicianpatient-pharmacist triangle. Data from literature shows that patients´ satisfaction with their treatments was linked with a higher success rate of treatment [36][37][38][39][40][41][42][43][44][45][46]. Our results highlight that patients who trust their pharmacist are more likely to evaluate their treatment efficiency.…”
Section: Patient´s Perception Regarding Cpp Requirementmentioning
confidence: 66%
“…Recent reviews also found that AWVs are a billable service that increased revenue. 17,21 Thus, AWVs, may be a starting point for billing in some practices. There are also opportunities to increase CCM billing for diabetes and other chronic conditions.…”
Section: Discussionmentioning
confidence: 99%